2016
DOI: 10.1155/2016/7637931
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Mediated Attenuation of Carbofuran Induced Oxidative Stress in Rat Brain

Abstract: The indiscriminate use of carbofuran to improve crop productivity causes adverse effects in nontargets including mammalian systems. The objective of this study was to evaluate carbofuran induced oxidative stress in rat brain stem and its attenuation by curcumin, a herbal product. Out of 6 groups of rats, 2 groups received two different doses of carbofuran, that is, 15 and 30% of LD50, respectively, for 30 days. Out of these, 2 groups receiving same doses of carbofuran were pretreated with curcumin (100 mg/kg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 31 publications
1
27
0
1
Order By: Relevance
“…Similar observations were recorded in the rat's kidney when the animals were exposed to CF (1 mg/kg) for consecutively 28 days (Kaur et al 2012) and also in the rat's brain stem when the animals were exposed to CF at two different doses, i.e. 15% (1.2 mg/kg) and 30% (2.4 mg/kg) of LD 50 for 30 days (Jaiswal et al 2016). Co-administration with turmeric, however, improved the activities of SOD and GSH-Px by scavenging superoxide and hydrogen peroxide produced by CF (Jaiswal et al 2015(Jaiswal et al , 2016.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar observations were recorded in the rat's kidney when the animals were exposed to CF (1 mg/kg) for consecutively 28 days (Kaur et al 2012) and also in the rat's brain stem when the animals were exposed to CF at two different doses, i.e. 15% (1.2 mg/kg) and 30% (2.4 mg/kg) of LD 50 for 30 days (Jaiswal et al 2016). Co-administration with turmeric, however, improved the activities of SOD and GSH-Px by scavenging superoxide and hydrogen peroxide produced by CF (Jaiswal et al 2015(Jaiswal et al , 2016.…”
Section: Discussionsupporting
confidence: 77%
“…15% (1.2 mg/kg) and 30% (2.4 mg/kg) of LD 50 for 30 days (Jaiswal et al 2016). Co-administration with turmeric, however, improved the activities of SOD and GSH-Px by scavenging superoxide and hydrogen peroxide produced by CF (Jaiswal et al 2015(Jaiswal et al , 2016. Curcumin, the main active ingredient of turmeric is potentially responsible in boosting these enzyme activities as confirmed by Jaiswal et al (2016).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…But the pretreatment of animals with curcumin showed attenuation of carbofuran toxicity because the activities of SOD and GSH of rat brain were significantly increased. The ameliorative effect of curcumin may be mediated via antioxidant potential of this molecule by scavenging the free radicals [17]. Moreover, curcumin treatment at both low and high doses significantly reduced levels of ROS and MDA and enhanced the activity of SOD and GSH-PX compared with the oxyhemoglobin group, and treatment with curcumin at both low and high doses significantly reduced the levels of TNF- α , IL-1 β , and IL-6 compared with the oxyhemoglobin group, suggesting that curcumin is protective against oxyhemoglobin induced neurotoxicity in an in vitro subarachnoid hemorrhage model and the protective effects of curcumin were mainly dependent on its attenuating oxidative stress, inflammation, and neuronal apoptosis [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that traditional Chinese herbs or formulae, such as puerarin [16], curcumin [17], and Buyang Huanwu Decoction [18], were popularly used to attenuate oxidative stress injury and protect endothelial cells from H 2 O 2 -induced apoptosis by inhibiting oxidative stress damage or ROS-mediated mitochondrial dysfunction. In traditional Chinese medicine, qi is an energy that can invigorate the body and enhance blood circulation and meridian circulation [19–21].…”
Section: Introductionmentioning
confidence: 99%